(untitled) (Global Journal of Science Frontier Research, 2012)
Use of tractor in Nigeria is characterised by various short comings which ranges from untimely tractor services, unsuitable landscape for tractor use, expensive tractor spare parts and unavailability of labour which has made commercial farming difficult. An option that might help farmers overcome this problem is animal traction. This study determined the attitude of farmers towards the use of animal traction technology in savannah zone of Oyo state, one hundred and forty four (144) respondents comprising 72 contact and 72 non-contact farmers were interviewed for the study. The relationships between respondents’ personal characteristics, farm characteristics and their attitudes towards the use of animal traction technology were determined using chi-square analytical tool. Finding revealed that majority of the respondents were males and married. They were literate and had fairly large family size. They were within active age range of 21-50 years and had over 20 years farming experience. They practiced mixed cropping, exhibited a neutral attitude towards the use of animal traction technology.